2014
DOI: 10.1007/s00405-014-2986-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of memantine on functional recovery of the facial nerve after crush injury

Abstract: The objective of this study is to establish whether memantine is an alternative and effective treatment on facial nerve recovery after crush injury, and also to analyze the effective doses of this promising agent. This is a randomized controlled animal study. 40 rats underwent crush injury to left main trunk of the facial nerve, and divided into 4 groups; (1) control (saline treated), (2) 5-mg/kg memantine, (3) 10-mg/kg memantine, and (4) 20-mg/kg memantine group. Facial nerve functions were evaluated by eye r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Although several medical therapies have been attempted in various facial nerve injury models, there is no accepted medical treatment for crush injuries. The current treatment options, aimed at reducing inflammation, have been gaining popularity 7, 8, 9. Vakharia et al (10) used the rat model to compare atorvastatin, sildenafil and darbapoetin on crush injury recovery and showed that the darbapoetin treated rats had more significant recovery in the first two weeks; all other measurements were insignificant 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several medical therapies have been attempted in various facial nerve injury models, there is no accepted medical treatment for crush injuries. The current treatment options, aimed at reducing inflammation, have been gaining popularity 7, 8, 9. Vakharia et al (10) used the rat model to compare atorvastatin, sildenafil and darbapoetin on crush injury recovery and showed that the darbapoetin treated rats had more significant recovery in the first two weeks; all other measurements were insignificant 10.…”
Section: Introductionmentioning
confidence: 99%
“…The current treatment options, aimed at reducing inflammation, have been gaining popularity. [7][8][9] Vakharia et al…”
Section: Introductionmentioning
confidence: 99%
“…Also, a neuroprotective effect of Memantine against rabbit model of optic nerve ischemia (18), rat model of retinal injury (48) and spinal cord injury (11) has been reported. The result of a recent study, conducted by Topdag et al in 2015, suggested that Memantine improves functional recovery of the facial nerve after crush injury (40). On the other hands, our unpublished data showed that early administration of Riluzole, a sodium channel blocker and anti-glutamatergic agent, after sciatic nerve crush could delay motor function recovery despite its well documented neuroprotective effect in the central nervous system (36,44).…”
Section: █ Discussionmentioning
confidence: 70%
“…Data were coded, tabulated using Statistical Package for Social Sciencesoftware computer program version 26 (SPSS, Inc., Chicago, IL, USA). (20)…”
Section: Immunohistochemical Histomorphometric and Statistical Analymentioning
confidence: 99%